Mastering the Old Testament ; v. 16B - McKenna, David Loren (Dallas, TX Word, 1994)
Contents : v. 16B : Isaiah 40-66. Includes bibliographical references.
Keywords: Bible. O.T. Isaiah XL-LXVI -- commentaries